Whole-Brain Vascular Architecture Mapping Identifies Region-Specific Microvascular Profiles In Vivo - Hohmann, Anja; Zhang, Ke; Mooshage, Christoph M.; Jende, Johann M.E.; Rotkopf, Lukas T.; Schlemmer, Heinz-Peter; Bendszus, Martin; Wick, Wolfgang; Kurz, Felix T. (American Journal of Neuroradiology, 2024)
BACKGROUND AND PURPOSE: The novel MR imaging technique of vascular architecture mapping allows in vivo characterization of local changes in cerebral microvasculature, but reference ranges for vascular architecture mapping parameters in healthy brain tissue are lacking, limiting its potential applicability as an MR imaging biomarker in clinical practice. We conducted whole-brain vascular architecture mapping in a large cohort to establish vascular architecture mapping parameter references ranges and identify region-specific cortical and subcortical microvascular profiles.MATERIALS AND METHODS: This was a single-center examination of adult patients with unifocal, stable low-grade gliomas with multiband spin- and gradient-echo EPI sequence at 3T using parallel imaging. Voxelwise plotting of resulting values for gradient-echo (R2*) versus spin-echo (R2) relaxation rates during contrast agent bolus administration generates vessel vortex curves that allow the extraction of vascular architecture mapping parameters representative of, eg, vessel type, vessel radius, or CBV in the underlying voxel. Averaged whole-brain parametric maps were calculated for 9 parameters, and VOI analysis was conducted on the basis of a standardized brain atlas and individual cortical GM and WM segmentation.RESULTS: Prevalence of vascular risk factors among subjects (n = 106; mean age, 39.2 [SD, 12.5] years; 56 women) was similar to those in the German population. Compared with WM, we found cortical GM to have larger mean vascular calibers (5.80 [SD, 0.59] versus 4.25 [SD, 0.62] P < .001), increased blood volume fraction (20.40 [SD, 4.49] s−1 versus 11.05 [SD, 2.44] s−1; P < .001), and a dominance of venous vessels. Distinct microvascular profiles emerged for cortical GM, where vascular architecture mapping vessel type indicator differed, eg, between the thalamus and cortical GM (mean, −2.47 [SD, 4.02] s−2 versus −5.41 [SD, 2.84] s−2; P < .001). Intraclass correlation coefficient values indicated overall high test-retest reliability for vascular architecture mapping parameter mean values when comparing multiple scans per subject.CONCLUSIONS: Whole-brain vascular architecture mapping in the adult brain reveals region-specific microvascular profiles. The obtained parameter reference ranges for distinct anatomic and functional brain areas may be used for future vascular architecture mapping studies on cerebrovascular pathologies and might facilitate early discovery of microvascular changes, in, eg, neurodegeneration and neuro-oncology.BMIbody mass indexBVFblood volume fractionCAcontrast agentCBIcapillary bed identifierCGIcaliber gradient indicatorcGMcortical gray matterCNcaudate nucleusGEgradient-echoGPglobus pallidusImaximum distance between the ascending and descending branches of the vascular hysteresis loopICCintraclass correlation coefficientKPSKarnofsky Performance StatusMNIMontreal Neurological InstituteQmicrovessel density parameterR2T2 relaxation raterCBVrelative CBVSAGEspin-and gradient-echoSEspin echoVAMvascular architecture mappingVHLvascular hysteresis loopVIPSvascular-induced bolus peak-time shiftVSIvessel size indexVTIvessel type indicator